ANALISIS FAKTOR LINGKUNGAN KERJA, KARAKTERISTIK INDIVIDU DAN ORGANISASI TERHADAP SEMANGAT KERJA GURU MTSN DI KABUPATEN BIREUEN PROVINSI ACEH - Zuryati, Zuryati; Ibrahim, Ibrahim (LPPM-UNIKI, 2023)
The research aims to analyze and obtain empirical input on the facts that occur in the research object relating to the influence of work environment factors, individual characteristics of teachers and school organizations on the work spirit of State Madrasah Tsanawiyah teachers (MTSN) in Bireuen Regency. In the form of a survey with data collection through questionnaires. Described quantitatively by analyzing the problem using a path analysis model. The results were found; 1) there is a causal relationship between work environment variables, individual characteristics of teachers and school organizations with an average correlation level of 0.475 or medium category, 2) there is a direct and indirect influence of the work environment on teacher morale of 36.05%. Meanwhile, individual characteristic factors were 57.87% and organizational factors were 52.91%. 3) Simultaneously the work environment, individual and organizational characteristics contribute 48,7% to teacher morale